Economic effects of the changing regime of autumn rains onto sheep breeding farms - Dono G.; Giraldo L.; Cortignani R. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
The change in the autumn rain regime can create problems for sheep breeding based on pasture or non-irrigated grass. A reduction in the useful rain hampers the growth of grass production, preventing grazing, and requiring farms to tap into the stock of hay to feed animals in the autumn-winter season. Farms may have to rent more land to produce grass in the spring in order to expand their forage production with an increase of costs that will be difficult to endure in a declining milk prices scenario. This analysis assesses whether the changes in climate variability, which are already under way, alter the probability distribution of rainfall in autumn, reducing the days of rain for the growth of grass. The economic effects of this and other changes will be evaluated by means of a Discrete Stochastic Programming territorial model that allows to represent the choices of farms under uncertainty; in this work we present a preliminary simulation concerning the effect of autumnal rainfall on sheep breeding. The analysis shows the different situation of a farm type that grows the grass completely non-irrigated, another with a limited supply of water from wells and a third that can tap into the water supply of a Water User Association.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)